2011
DOI: 10.1245/s10434-011-2172-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Ultrasound is Not Useful for Identifying Nodal Metastasis in Melanoma Patients Undergoing Sentinel Node Biopsy: Preoperative Ultrasound in Clinically Node-Negative Melanoma

Abstract: Background Sentinel lymph node biopsy (SLNB) is widely used in melanoma. Identifying nodal involvement preoperatively using high-resolution ultrasound may offer less invasive staging. This study assessed feasibility and staging results of clinically-targeted ultrasound (before lymphoscintigraphy) compared to SLNB. Methods From 2005–2009, 325 patients with melanoma underwent ultrasound before SLNB. We reviewed demographics and histopathologic characteristics, then compared ultrasound and SLNB results. Sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…When compared to the literature, the sensitivity in our hands (51%) is significantly higher than previously reported rates, which differ from 4% to 39% [24][25][26][27][28][29]. In these relatively small series, Starritt et that high-resolution ultrasound (HRUS) yielded a sensitivity of 12% (2/17) [28].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…When compared to the literature, the sensitivity in our hands (51%) is significantly higher than previously reported rates, which differ from 4% to 39% [24][25][26][27][28][29]. In these relatively small series, Starritt et that high-resolution ultrasound (HRUS) yielded a sensitivity of 12% (2/17) [28].…”
Section: Discussioncontrasting
confidence: 68%
“…In these relatively small series, Starritt et that high-resolution ultrasound (HRUS) yielded a sensitivity of 12% (2/17) [28]. Chai et al demonstrated a sensitivity of 34%, but only 10 patients (3.4%) could undergo US-FNAC prior to the surgical SN in their study [29]. The preliminary results of one larger series, pre-SN US-FNAC in the MSLT-2 study, reported sensitivity of merely 4.2% (8/193) [24].…”
Section: Discussionmentioning
confidence: 86%
“…Occult lymph node metastasis is present in 15-20% of patients with melanoma of the head and neck and clinically negative nodes. According to Chai et al [24], preoperative ultrasound (US) is not useful for identifying nodal metastasis in clinically node-negative melanoma patients undergoing sentinel node (SN) biopsy. In 471 patients, the overall sensitivity of US was 33.8%, specificity 85.7%, positive predictive value 36.5%, and negative predictive value 84.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity appeared to improve somewhat with increasing Breslow depth. Sensitivity was highest for the neck, but specificity was highest for the groin [24]. However, the combination of preoperative US and US-guided FNA cytology can identify 65% of SN metastases and thus reduce the need for surgical SN procedures [25].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that routine preoperative US in clinically node-negative melanoma is impractical because of its low sensitivity, but selected patients with thick or ulcerated lesions may benefit. However, because of variable lymphatic drainage patterns, preoperative US without lymphoscintigraphic localization will provide incomplete evaluation in many cases (28). These data can be extrapolated for patients in the follow-up setting given the low sensitivity of US in clinically node-negative patients.…”
Section: Lymph Node Ultrasonographymentioning
confidence: 99%